Marine mollusk biodiversity in Northeastern Islands of Vietnam, impact factors and proposing conservation solutions - Sarti, Massimo; Thung, Do Cong; Nguyen Dang, Ngai; Dau Van, Thao; Cao Thi Thu, Trang; Dao Minh, Dong; Calcinai, Barbara; Cerrano, Carlo (Vietnam Journal of Marine Science and Technology, 2023)
A biodiversity and water-quality monitoring campaign was conducted in the Northeastern Archipelago of Vietnam, including Quang Ninh Province and Hai Phong, in 2017–2018. Mollusks are selected as the critical proxy indicator, and water-quality parameters are tested against National acceptability standards. The study revealed that, despite declining trends over the past two decades, mollusks are still highly diverse, with 647 species belonging to 227 genera, 95 families, and five classes (76% of all the species identified in the Tonkin Gulf). Of these, 253 species of 39 families (39% of the whole stock) are of high economic value, supporting an active trade in the region and thousands of livelihoods. Several species (abalone, blood cockle, green mussel, pearl oysters, Pacific oysters, double-headed clams, Asian hard clams, white clams, and squids) are intensively farmed. However, aquaculture still needs to be derdeveloped as capture from the wild is preferred. Water quality is unexpectedly high despite impacting factors such as urban development, industry, mass tourism, and demographic increase, mainly within the limits of acceptability set by the Government. Salinity, pH, and temperature are compatible with marine life, and a limited impact is represented by dissolved nitrates and suspended hydrocarbons in suspension. Despite favorable conditions of the aquatic environment, biodiversity decline has been a steady trend over the past decade. The causes are the urban encroachment over the coastal tract, the intertidal spawning grounds, breeding grounds, and nurseries, overexploitation, IUU fishing, lack of management, and failed establishment of conservation areas and MPAs. Spawning and breeding grounds identification and demarcation, their participated co-management, investments in environmental protection, technologies, and capacity building, and promotion of aquafarming of marketable species are among the measures recommended to be implemented with priority, to relieve the pressure over the wild stock and promote regeneration. The role of science in monitoring and detecting environmental changes guiding the adoption of proactive measures to prevent depletion and stock collapse, is the pathway to the sustainability of resource use and human well-being.